Postoperative mortality in New Zealand following general anaesthetic: demographic patterns and temporal trends - James Stanley; Sarah Jackson; Jason K Gurney; Melissa McLeod; Doug Campbell; Luke Boyle; Elizabeth Dennett; Jonathan Koea; Dick Ongley; Diana Sarfati (BMJ Open)
Objectives In this manuscript, we describe broad trends in postoperative mortality in New Zealand (a country with universal healthcare) for acute and elective/waiting list procedures conducted between 2005 and 2017.Design, participants and setting We use high-quality national-level hospitalisation data to compare the risk of postoperative mortality between demographic subgroups after adjusting for key patient-level confounders and mediators. We also present temporal trends and consider how rates in postoperative death following acute and elective/waiting list procedures have changed over this time period.Results and conclusion A total of 1 836 683 unique patients accounted for 3 117 374 admissions in which a procedure was performed under general anaesthetic over the study period. We observed an overall 30-day mortality rate of 0.5 per 100 procedures and a 90-day mortality rate of 0.9 per 100. For acute procedures, we observed a 30-day mortality rate of 1.6 per 100, compared with 0.2 per 100 for elective/waiting list procedures. In terms of procedure specialty, respiratory and cardiovascular procedures had the highest rate of 30-day mortality (age-standardised rate, acute procedures: 3–6 per 100; elective/waiting list: 0.7-1 per 100). As in other contexts, we observed that the likelihood of postoperative death was not proportionally distributed within our population: older patients, Māori patients, those living in areas with higher deprivation and those with comorbidity were at increased risk of postoperative death, even after adjusting for all available factors that might explain differences between these groups. Increasing procedure risk (measured using the Johns Hopkins Surgical Risk Classification System) was also associated with an increased risk of postoperative death. Encouragingly, it appears that risk of postoperative mortality has declined over the past decade, possibly reflecting improvements in perioperative quality of care; however, this decline did not occur equally across procedure specialties.